Municipal governments and forest management in lowland Bolivia - Kaimowitz, D.; Vallejos, C.; Pacheco, P.; Balanza, P.P.; López, R. (1998)
Recent decentralization and forestry laws in Bolivia give municipal governments a strong role in forest management. This article analyzes the impact of those laws on local government activities related to logging, protected areas, indigenous territories, and land-use planning. It con-cludes that the laws have created new opportunities for indigenous people, small farmers, and small-scale timber producers to gain access to forest resources and influence forest policy, although they are not always able to take advantage of those opportunities. The article identifies both positive and negative trends with regard to the laws' impact on resource management, although it is premature to draw firm conclusions.